Kebijakan Fiskal Moneter Inflasi dalam Perspektif Ekonomi Islam - Elsa Juanda; Erika Tasya Salsabila; Muhammad Sidik; Faisal Hidayat (Pusat Riset dan Inovasi Nasional, 2024)
Inflation is the general rate of increase in prices. Inflation occurs due to several things including natural inflation, human error inflation, cost push inflation, spiralling inflation, imported inflation. In Indonesia inflation continues to rise and the socio-economic gap is widening. inflation occurs in Indonesia unevenly. Bank Indonesia as the highest monetary authority in Indonesia has a goal to achieve and maintain the stability of the rupiah. This research aims to find out and understand how to overcome inflation with an Islamic economic perspective. This research is a qualitative research with literature study method. The literature method is an activity related to the method of collecting prices that usually (generally) experience a continuous increase in library data, by reading and recording, and managing research materials. Activities to collect data by searching and collecting various books, journals, and scientific articles that contain the concept under study, to be reviewed and produce conclusions. The way to overcome inflation in the perspective of Islamic economics is by implementing fiscal policy, monetary policy and other policies.